2012
DOI: 10.1097/jgp.0b013e31825d091a
|View full text |Cite
|
Sign up to set email alerts
|

Depression Interventions Among Racial and Ethnic Minority Older Adults: A Systematic Review Across 20 Years

Abstract: While there is strong evidence in support of geriatric depression treatments, much less is available with regard to older U.S. racial and ethnic minorities. The objectives of this review are to identify and appraise depression treatment studies tested with samples of U.S. racial and ethnic minority older adults. We include an appraisal of sociocultural adaptations made to the depression treatments in studies meeting our final criteria. Systematic search methods were utilized to identify research published betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 59 publications
(156 reference statements)
0
31
0
Order By: Relevance
“…A systematic review of 23 effective models revealed that most were multi-component and included care management and a behavioral approach such as problem solving, cognitive behavioral or behavioral activation therapies, addressed unmet needs and provided participants specific skills to cognitively reframe and manage situational stressors such as poor health, housing or social needs (Gitlin, in press). These models are unified in their attempts to identify and tackle the multiple contextual factors that may contribute to or reinforce poor mood and which drug treatments cannot address (Frederick et al, 2007; Fuentes & Aranda, 2012; Gitlin, in press). …”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 23 effective models revealed that most were multi-component and included care management and a behavioral approach such as problem solving, cognitive behavioral or behavioral activation therapies, addressed unmet needs and provided participants specific skills to cognitively reframe and manage situational stressors such as poor health, housing or social needs (Gitlin, in press). These models are unified in their attempts to identify and tackle the multiple contextual factors that may contribute to or reinforce poor mood and which drug treatments cannot address (Frederick et al, 2007; Fuentes & Aranda, 2012; Gitlin, in press). …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, little is known about the effectiveness of depression treatment interventions among older American Indians. 57 Future studies are warranted to evaluate the impact of existing depression treatments in this population.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we excluded studies not focused on AI/AN/NH health that found no AI/AN/NH literature and made no assertions about AI/AN/NH populations (Fuentes and Aranda 2012; Jaja et al 2008; Park and Taylor 2007). We also excluded others not focused on AI/AN/NH health that found AI/AN/NH literature but did not discuss it in the AI/AN/NH context, did not present the AI/AN/NH results separately, and drew no AI/AN/NH-specific inferences (Herbst et al 2005).…”
Section: Discussionmentioning
confidence: 99%